PENGEMBANGAN MEDIA PEMBELAJARAN BERUPA KOMIK BIOLOGI PADA MATERI SISTEM PENCERNAAN MAKANAN UNTUK SISWA KELAS XI IPA - Lova, Ridhatul Rahayu; Fifendy, Mades; Sudirman, Sudirman (STKIP PGRI Sumbar, 2013)
ABSTRACTTeachers in the learning process not only uses textbooks or supporting , but also can use other learning media to help smooth the process of learning. This study aims to produce a comic media learning biology valid and practical. This type of research is the development of research by using 4-D models that consists of 4 stages, stage definition (define), design (design), development (develop), and the spread (disseminate), do not disseminate stage. The study was conducted in the second semester of academic year 2012/2013. Of this study generated media such as comics biology lesson on the digestive system of food material for students of class XI IPA valid and very practical. The validity of 83.1% with a valid criteria, while practicalities value 86.25% of teacher with very practical criteria, and the practicalities value 86.01% Â of students with very practical criteria.Â